Pengaruh Absensi, Motivasi, Kedisiplinan, Lingkungan Kerja, Keselamatan Kerja Terhadap Kinerja Karyawan pada CV.Yhuen Garment Boyolali. - Gunadi, Wahyu Tri; , Sri Murwanti, SE. M.M (2017)
This research was conducted in CV.Yhuen Garment Boyolali aimed to investigate the influence of the performance of the attendance, motivation, discipline, working environment, safety of employees. This study uses the survey design, the research took a sample of employees CV.Yhuen Garment Boyolali using questionnaires as a data collection tool. The analytical tool used in this research is to test the instrument, the classical assumption test, data analysis (Multiple linear regression analysis, t test, F test and the coefficient of determination (R2)). The results of this study a significant difference between the attendance, motivation, discipline, work environment, work safety to employees performance.